The Effect of Problem Based Learning Model on Mathematical Critical Thinking Ability of Students of Class X SMA Negeri 2 Pematangsiantar - Panjaitan, Riris Novitasari; Sidabutar, Ropinus (Lembaga Riset Mutiara Akbar, 2022)
The purpose of this study was to determine the effect of using the Problem Based Learning learning model on the mathematical critical thinking skills of class X SMA Negeri 2 Pematangsiantar. The research design used a posttest only control group design. The population in this study were all students in class X SMA Negeri 2 Pematangsiantar T.A 2022/2023, and the sample in this study was all students in class X MIPA 5 SMA Negeri 2 Pematangsiantar T.A 2022/2023 totaling 36 students. The instruments used in this study were validity, reliability, difficulty level of the test items and the discriminating power of the test items. The data obtained was then analyzed using data analysis techniques to obtain an average value of the Problem Based Learning learning model 38.44 and an average mathematical critical thinking ability of 36.94. The results of the hypothesis test after obtaining tcount = 6.551 and ttable = 2.032 and the contribution of Problem Based Learning to students' mathematical critical thinking skills is 0.5580 (55.8%). Based on this description, it was concluded that the use of the Problem Based Learning learning model had an influence on students' mathematical critical thinking skills in learning the system of three-variable linear equations in class X SMA Negeri 2 Pematangsiantar